The Effectiveness of Using A Maternity Pillow and Coffee Aromatherapy on Sleep Quality in Third-Trimester Pregnant Women - Ika Lestari Sitorus; Selvi Puspan Sari; Ellysyah Husein Damanik (Indonesian Journal of Global Health Research, 2025)
Decreased sleep quality in pregnant women can inhibit the body's detoxification process, causing physical and emotional health disorders, such as unstable moods, fatigue, and hormonal disorders. This condition is at risk of affecting fetal development. One effort that can be made to improve sleep quality is the use of maternity pillows and aromatherapy coffee Objective: This study aims to analyze the effectiveness of the use of maternity pillows and aromatherapy coffee in improving the sleep quality of pregnant women in the third trimester. Method: This study used a quasi-experimental design with a one-group pre-test and post-test without control approach. The study sample consisted of 31 pregnant women in the third trimester who experienced sleep disorders, taken using the total sampling technique. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) questionnaire before and after the intervention. Data analysis was carried out using the Wilcoxon test. Results: Before the intervention, all respondents (100%) had poor sleep quality. After using a maternity pillow and aromatherapy coffee, 74.2% of respondents reported good sleep quality. The Wilcoxon test showed a significant difference between sleep quality before and after the intervention (p <0.05). Conclusions: The use of maternity pillows and aromatherapy coffee has been proven effective in improving the sleep quality of pregnant women in the third trimester. This method can be recommended as a non-pharmacological alternative to overcome sleep disorders in pregnant women.